Evaluating the Discontinuation of India’s Supply-Side Affordable Housing Policy for Slum Redevelopment Through Frank Fischer’s Lens - Tapadia, Dhruv; Soladhara, Tithi; Kulsheshtra, Shelly; Lunawat, Rishita (Journal of Contemporary Urban Affairs, 2025)
India’s In-Situ Slum Redevelopment (ISSR) vertical of the Pradhan Mantri Awas Yojana-Urban was terminated in September 2024 after delivering barely one-quarter of its sanctioned dwellings. This study interrogates that discontinuation through Frank Fischer’s four-tier public-policy framework, integrating secondary data, national audits and 109 household surveys across four ISSR sites in Ahmedabad. Contextual analysis confirms that ISSR targeted a genuine housing deficit in agglomerated labour markets, yet technical verification reveals only 23 % completion and persistent infrastructure gaps. Situational validation highlights post-occupancy cost spirals, dysfunctional resident-welfare associations and a statistically significant link (χ² = 53.4, p < 0.001) between governance quality and maintenance-fee compliance. Societal vindication exposes vertical “poverty traps”: 62 % of households face higher living expenses and 41 % report lost informal livelihoods. Ideological review finds the developer-led model over-estimated land-value capture and under-valued community stewardship, echoing global evidence from Jakarta and Cairo. The study concludes that ISSR’s failure stems from misaligned economic incentives, weak institutional capacity and neglect of behavioural adaptation. Re-imagined supply-side programmes must pair incremental upgrading and portable subsidies with enforceable post-occupancy governance to preserve agglomeration benefits while ensuring social equity. Findings offer transferable lessons for secondary Indian cities planning future slum-housing interventions.